Correlates of trichomoniasis among female sex workers who inject drugs in two Mexico-US border cities. (August 2020) - West, Brooke S; Becerra Ramirez, Milagros; Bristow, Claire C; Abramovitz, Daniela A; Vera, Alicia; Staines, Hugo; Gudelia Rangel, M; Patterson, Thomas L; Strathdee, Steffanie A
This paper evaluates correlates of trichomoniasis among female sex workers who inject drugs (FSWIDs) in two Mexico-US border cities. HIV-negative FSWIDs aged 18 years or older were enrolled in a study between 2008 and 2010 in Tijuana and Ciudad Juarez (Cd.), Mexico. All participants underwent a baseline interviewer-administered survey and did a rapid test for trichomoniasis. Using regression to estimate prevalence ratios, we examined sociodemographics, sex work characteristics, sexual health and behavior, substance use, and police and violence exposures as potential correlates of trichomoniasis. Of 584 women (284 in Tijuana, 300 in Cd. Juarez), prevalence of trichomoniasis was 33.6%. Factors associated with trichomoniasis in multivariable analysis were having money stolen by police in the past six months (adjusted prevalence ratio [aPR] =1.448, 95% confidence interval [CI] = 1.152–1.821), recent methamphetamine use (aPR = 1.432, CI = 1.055–1.944), lifetime syphilis infection (aPR = 1.360, CI = 1.061–1.743), ever use of a home remedy to treat vaginal symptoms (aPR = 1.301, CI = 1.027–1.649), and number of regular clients in the past month (aPR = 1.006 per client, CI = 1.004–1.009), while controlling for age and city of interview. Alongside the need for trichomoniasis surveillance and treatment programs, findings indicate that both structural and behavioral factors serve as primary correlates of trichomoniasis among FSWIDs in these cities.